Simultaneous differential detection of canine blood parasites: Multiplex high-resolution melting analysis (mHRM) - Kittisak Buddhachat (2020)
© 2020 Elsevier GmbH Recently, the incidence of canine infection by the tick-borne parasites Babesia spp., Hepatozoon canis, Ehrlichia canis and Anaplasma platys has been increasing globally. We have developed a multiplex high-resolution melting analysis (mHRM) technique to reduce the time demands and costs associated with detecting haemoparasites in canine blood, while increasing the degree of reliability of this method of analysis. We have designed primers that are specific for protozoans (B. vogeli and H. canis) and Rickettsia-like bacteria (E. canis and A. platys) based on the 18S or 16S rDNA sequences, respectively. Two primer pairs (Protz18S-C and Bact16S-A) were found to be suitable for detecting these agents since their melting temperatures (Tm) exhibited discernible differences among the four haemoparasites, A. platys, B. vogeli, E. canis and H. canis (83.10 °C, 82.41 °C, 80.37 °C and 78.56 °C, respectively). The sequences acquired from these PCR products were >94 % identical to those of A. platys, B. vogeli, E. canis and H. canis in GenBank. The limit of detection (LOD) for B. vogeli, E. canis and A. platys was 103 copies/μl, while the LOD for H. canis was 104 copies/μl. Of the 68 dogs tested, 28 (41 %) were infected with these agents. The most commonly occurring infection involved E. canis, followed by B. vogeli, A. platys and H. canis, with infection percentages of 26 %, 13 %, 7 % and 6 %, respectively. These results demonstrate that mHRM can serve as a rapid, economical and reliable tool for the detection of parasitic diseases in canine blood for diagnosis and epidemiology.